2018
DOI: 10.3390/molecules24010053
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Vitamin D and Its Potential Role in the Prevention and Treatment of Type 1 Diabetes Mellitus—A Narrative Review

Abstract: Type 1 diabetes mellitus is a chronic autoimmune disease associated with degeneration of pancreatic β-cells that results in an inability to produce insulin and the need for exogenous insulin administration. It is a significant global health problem as the incidence of this disorder is increasing worldwide. The causes are still poorly understood, although it certainly has genetic and environmental origins. Vitamin D formed profusely in the skin upon exposure to sunlight, as well as from dietary sources, exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
22

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 151 publications
(195 reference statements)
0
56
0
22
Order By: Relevance
“…In adolescents, many studies revealed no association between 25(OH)D level and onset of T1DM [102][103][104]. However, there is a clear effect of vitamin D in young adults, as low 25(OH)D levels were significantly associated with developing T1DM [105]. However, according to the available literature, the cause-and-effect relationship is inconclusive.…”
Section: Diabetesmentioning
confidence: 99%
“…In adolescents, many studies revealed no association between 25(OH)D level and onset of T1DM [102][103][104]. However, there is a clear effect of vitamin D in young adults, as low 25(OH)D levels were significantly associated with developing T1DM [105]. However, according to the available literature, the cause-and-effect relationship is inconclusive.…”
Section: Diabetesmentioning
confidence: 99%
“…Accumulating evidence has emerged for an association between vitamin D status and T1DM risk [225]. Modulated by activation of the VDR, vitamin D influences several metabolic pathways and affects the immune system.…”
Section: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…A deficit of vitamin D is associated with increased risk of autoimmune diseases, including T1D. Vitamin D has immunomodulatory effects and the relative molecular mechanisms as well as the clinical studies on the use of vitamin D in T1D were extensively reviewed [122,123]. A potential protective effect of vitamin D against the development of T1D was supposed and it may be due to the suppression of insulitis by modification of CD8+ and CD4+ T-cells, B lymphocytes, and macrophage infiltration [124,125].…”
Section: Vitamin Dmentioning
confidence: 99%